Cardiogenic Shock and Hyperinflammatory Syndrome in Young Males With COVID-19. (October 2020) - Chau, Vinh Q.; Giustino, Gennaro; Mahmood, Kiran; Oliveros, Estefania; Neibart, Eric; Oloomi, Mehdi; Moss, Noah; Mitter, Sumeet S.; Contreras, Johanna P.; Croft, Lori; Serrao, Gregory; Parikh, Aditya G.; et al.
Abstract : Supplemental Digital Content is available in the text.